2019
DOI: 10.3389/fpls.2018.01870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Doses of Organic Extract-Based Biostimulant on Greenhouse Lettuce Grown Under Increasing NaCl Concentrations

Abstract: The enhancement of plant tolerance toward abiotic stresses is increasingly being supported by the application of biostimulants. Salinity represents a serious problem in the Mediterranean region. To verify the effects deriving from the application of biostimulants, trials on Romaine lettuce plants under salt exposure were performed, in greenhouse. Plants were subjected to three NaCl solutions with 0.8, 1.3, and 1.8 dS/m of electrical conductivity. The volume of the solution was 200 mL/plant and delivered every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 80 publications
2
31
0
Order By: Relevance
“…Treated plants also have a higher performance and an increased maximum quantum efficiency of PS2 compared to the control. Similar results have been recently observed in lettuce plants in response to the application of an organic commercial biostimulant named Retrosal ® [162].…”
Section: Biostimulants and Salinity Stresssupporting
confidence: 88%
“…Treated plants also have a higher performance and an increased maximum quantum efficiency of PS2 compared to the control. Similar results have been recently observed in lettuce plants in response to the application of an organic commercial biostimulant named Retrosal ® [162].…”
Section: Biostimulants and Salinity Stresssupporting
confidence: 88%
“…Cheynier et al 47 advanced a research hypothesis that proline synthesis may be accompanied by additional NADPH oxidation. As a consequence of the above, the increased NADP+NADPH ratio can determine the enhanced activity of the oxidative pathway of pentose phosphate, thereby assuring precursors for the phenolic biosynthesis via the shikimic acid pathway 41,48 . A study conducted by Rouphel et al 49 demonstrated proline concentration in biostimulant treated plants to contribute to better osmotic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in chlorophyll content usually correlates with an increase in photosynthesis and subsequent increase in plant biomass [ 103 ]. It is well-documented that under saline stress conditions, chlorophyll content decreases [ 64 , 104 , 105 , 106 , 107 ]. In several reports, PB treatment led to a significant increase in total chlorophyll [ 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%